Factors Affecting Physical Activity During Pregnancy: A Scoping Review - Aulia Kurnianing Putri; Luluk Rosida; Faizatul Ummah (Jurnal MIDPRO, 2021)
ABSTRACTPregnancy is an important period before delivery. The findings in several studies mentioned that pregnant women complained of discomfort. One of the solutions is by doing pregnancy exercise. This scoping review aimed to investigate factors affecting pregnant women in carrying out physical activities during pregnancy. It applied the Arksey and O'Malley framework which developed using the PEO framework. The articles were selected through relevant databases, namely Pubmed, Wiley, Ebsco and gray literature from Google Scholar. The results showed that factors affecting pregnant women in doing physical activity included maternal education, maternal physical activity habits before pregnancy, peer influence, healthy motivation and family support, husband, facilitator, and adequate facilities. While the inhibiting factors were lack of free time, lack of information, fatigue, pregnancy symptoms, and lack of motivation. It can be concluded that physical activity during pregnancy which were carried out according to the guidelines and needs is proven to provide optimal health benefits and fitness during the pregnancy process and reduce the risk of delivery with assistive devices or by caesarean section.  Keyword: Pregnancy, Factor or Cause, Physical Activity